PENGARUH BOARD STRUCTURE TERHADAP EARNINGS MANAGEMENT MELALUI INTELLECTUAL CAPITAL DISCLOSURE SEBAGAI VARIABEL MEDIASI (STUDI PADA PERUSAHAAN PERBANKAN TAHUN 2011-2016) - Felicia Oetomo; Saarce Elsye Hatane (Business Accounting Review, 2018)
This study aims to determine the direct impact of board structure on earnings management. In addition, this study also aims to determine the indirect impact of the board structure on earnings management using intellectual capital disclosure as a mediating variable. The sample constituted of 42 banking companies listed on Indonesia Stock Exchange during the period of 2011-2016. The data was collected from annual reports, which were then analyzed using WarpPLS version 5.0 software.            The finding revealed that there is no significant impat of board structure on earnings management, positive impact of board structure on intellectual capital disclosure, and negative impact of intellectual capital disclosure on earnings management. Furthermore, this study also found that intellectual capital disclosure is able to mediate the impact of board structure on earnings management.